PlasPI marine cameras: Open-source, affordable camera systems for time series marine studies. (April 2020) - Purser, Autun; Hoge, Ulrich; Lemburg, Johannes; Bodur, Yasemin; Schiller, Elena; Ludszuweit, Janine; Greinert, Jens; Dreutter, Simon; Dorschel, Boris; Wenzhöfer, Frank
Graphical abstract: Abstract: Imaging underwater can be particularly problematic and expensive given the harsh environmental conditions posed by salinity and for some deployments, pressure. To counter these difficulties, expensive waterproof pressure resistant housings are often used, commonly built from expensive materials such as titanium, if intended for long duration deployments. Further, environmental investigations often benefit from replicate data collection, which additionally increases study costs. In this paper we present a new camera system, developed with off the shelf and 3D printed cost effective components for use in shallow waters of <150 m depth. Integrating Raspberry Pi Zero W microcomputers with open source design files and software, it is hoped these camera systems will be of interest to the global marine and freshwater research communities.